2004
DOI: 10.1007/s10388-004-0014-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of steroid therapy on postoperative course and survival of patients with thoracic esophageal carcinoma

Abstract: Background. Perioperative steroid therapy has been shown to be safe and effective in inhibiting the production of inflammatory mediators and reducing postoperative hospital morbidity. However, there is limited information to show the effect of steroid therapy on long-term survival. In this study we evaluated the effect of perioperative steroid therapy on long-term survival of patients with thoracic esophageal cancer. Methods. Between 1993 and 2000, 141 consecutive patients with primary thoracic esophageal canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
(46 reference statements)
0
10
0
Order By: Relevance
“…The included studies reported on a variety of eight cancer types: pancreatic adenocarcinoma [19,28], non-small-cell lung cancer [20,23,34], ovarian [21], rectal [22,33], colorectal [25,31], endometrial [26], oesophageal [27,29,30,32], and breast cancer [24]. Sample sizes range from 37 [27] to 2628 [24] patients and the follow-up periods from six months to ten years.…”
Section: Study and Patient Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…The included studies reported on a variety of eight cancer types: pancreatic adenocarcinoma [19,28], non-small-cell lung cancer [20,23,34], ovarian [21], rectal [22,33], colorectal [25,31], endometrial [26], oesophageal [27,29,30,32], and breast cancer [24]. Sample sizes range from 37 [27] to 2628 [24] patients and the follow-up periods from six months to ten years.…”
Section: Study and Patient Characteristicsmentioning
confidence: 99%
“…One of these was analysed as two separate studies, and will be referred to as two studies, because the participants were divided into two study populations according to lymph node dissemination [25]. Fifteen studies reported OS [19,20,[22][23][24][25][26][27][28][29][30][31][32][33] and seven studies reported DFS [20,23,26,[31][32][33][34]. Several studies reported recurrence-free survival or progression-free survival; however, this definition was in accordance with our predetermined definition of DFS and was analysed as such.…”
Section: Study and Patient Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations